PG28 Just in time: developing a micro-simulation training programme. (10th November 2020) - Patel, Tulsi; Jones, Rachel; Trippick, Sarah; Baki, Yasmin
Abstract : Introduction: Due to COVID-19 all acute paediatric services and staff were relocated from UCLH. Despite redirection pathways, children continued to present to the Emergency Department (ED). A learning needs analysis identified a requirement to rapidly upskill the ED nursing and medical team. As a result, paediatric ED fellows and nurse educators designed an adaptable and rapidly deliverable simulation training model to meet a range of training needs. Secondary objectives of this project were to identify any latent safety threats relating to paediatric patients. Methods: We designed four low-fidelity, in-situ scenarios. Learning objectives were the initial management of an unwell child and familiarising staff with equipment and the environment. Sessions were restricted to a maximum of six participants to enable social distancing. Short 30 minute sessions were scheduled after morning handover to encourage participation and minimise disruption to the working environment. Participants completed a post-session feedback questionnaire. Results: 78 participants (26 medical, 52 nursing) attended at least one of 16 simulations over a 4 week period. Participants appreciated learning in small multi-disciplinary (MDT) groups in a non-judgemental environment. 99% reported that this was a supportive learning environment. As faculty were familiar with participants, the scenarios were adapted to meet individual learning needs depending on the mix of participants at each session. Faculty noted that the low-fidelity simulations reduced distractions and focused attention on key objectives. Sessions were easy to plan and set-up, enabling delivery of multiple simulations in a short timeframe. Environmental threats were identified and addressed in a timely manner. Discussion: ED staff were intrinsically motivated to participate in this programme as they identified a gap in knowledge and skills. By maintaining small groups we created a safe learning space, encouraging participant engagement without the fear of performing in front of an audience. Gaining early 'buy-in' from nursing and medical leads and holding short, regular sessions enabled the programme to become embedded in the department's culture, thus encouraging participation. By designing simple scenarios with focused learning objectives, we were able to ensure a consistent standard of delivery whilst adapting sessions to meet individual learning needs. Faculty noted the importance of role-modelling a good multi-disciplinary working relationship for the participants. This approach has established an MDT training culture of the department and helped foster positive relationships between staff members. This simulation model enabled us to train large numbers of staff over a short period of time under challenging and novel conditions.